Toplu Konut Yerleşmelerinde Çevre Standartlarının Değerlendirilmesi (bahçeşehir Örneği) - Ancın, Ö. Neslihan (Fen Bilimleri Enstitüsü, 1995)
Çağımızın insanı her geçen gün kendisini doğadan uzaklaştıran mimari yapılar içinde nedenli konfor içinde bulunursa bulunsun daima doğanın hasretini çekerek her fırsatta doğa ile bütünleşmek istemektedir. Bu nedenle toplu konutlar ve yeşil alanlar planlanırken insanların ihtiyaçlarını karşılamak temel ilkeler arasında yer almal ı d ı r. Zamanımızda konut sadece bir barınak olarak görülmeyip mahremiyeti, dostluğu, mutluluğu sağlayan bir araç ve yaşama çevresi, teknik ve sosyal alt yapısı ile bir bütün olarak görülmeye başlanmıştır. Çalışmada toplu konut yerleşmelerinin insanların ihtiyaçlarına en iyi cevap verebilmesi için doğal ve yapay çevresinin niteliklerinin ne olması gerektiği ve gerek Türkiye'de gerekse yabancı ülkelerde bu konuda saptanan standartlar araştırılmıştır. Çalışmada Türkiye'deki büyük toplu konut uygulamalarından biri olan Bahçeşehir Toplu Konutu incelenerek, yerinde anket çalışmaları ile uygulanan standartlar araştırılarak Türkiye'deki ve yabancı ülkelerdeki standartlarla karş ı laşt ı r ı İm ı şt ı r. Bu değerlendirmelere göre saptanan eksiklikler sonuç bölümünde belirtilerek eksikliklerin giderilmesi için gereken önlem ve önerilere yer verilmiştir.

Through out history, human beings developed housing forms of different types and dimmension depending on their needs such as life style, and natural environment conditions. Shelter is still a very important problem because of the fast increase in population, and fast urbanization. Thus, mass housing especially in urban areas have gained import ans in the last decades. This study consists of an introduction and five consequent parts. In the first part, the importance of the subject is dealt with and the aim of this master thesis is emphasised. In the second part, the definition of housing and mass housing are made and the history and the applications of mass housing are reviewed. In the third part, the definition of environment is made and further it is noted that two types of environment can be distinguished: Natural and man-made environment. Elements of natural environment are topography, climate conditions, ground conditions (soil, dept. to water table, ve j etation ) : Natural environment elements play a most important part in determinating the appropriateness of the location and design of a site. They determine the value of land, the number of dwelling units proposed and whether these are to be apartments, flats, row or town houses, the orientation and spacing of buildings, the method of waste colecttion and disposal and the landscape development and the preservation of existing trees. All thes factors must be xii correlated to produce a simple livable economical pattern of land use in which the land and buildings are integrated and so organized ea to serve the needs of the families to be housed. Elements of man made environment are administrative facilities, educational facilities social and cultural facilities, health facilities, commercial facilities, trasportation systems, utility systems, city furnitures, and green areas: Administrative facilities contain facilities that provide management of settlements and units that give general and special services. While administrative facilities bring general programs and politics of the government, at the same time they conduct local problems to the government. Variation and numbers of these facilities change according to administrative organization grades Educational facilities take an important part in fixing settlement systems and determinating largeness of settlements. They include preschools and formal schools, high schools. While nursery school is planned for prekindergarten activities, kinder garten is considered as proporatory to starting formal education. Elementary school is considered one of the basic organizational elements of reighborhoord. These facilities must be within safe walking distance, ideally, the children should have walking access without having to cross any vehicular streets. Social and cultural activities help people to progress themselves to get used to improve their life conditions and to get rid of feeling of lonelines. Facilities that provide such activities are conmunity centers, youth centers, public library, social clubs, theathers, cinemas, mosques, defferent kinds of associations, e.t.c. Numbers and variations of these facilities depend on the population of the settlement, social class and its characteritics. Health facilities which give medical treatment and potect community health include hospitals, polyclinics, dispensary, mather-cild health centers, health homes etc. These facilities change according to population. When population increases the number and variation of health facilities increase as well. Commercial facilities which are near the settling areas are centers that people satisfy their daily, weekly and monthly need and, have mutual commercial relationships there to. Commercial facilities are classifield according to population and necessity. It is very important that these xiii commercial facilities must be constructed in the center of the settlement. Transportation system is one of the important subject that porvides accessibility and livability of settlements. On housing sites, it is important to maintain a practical way for free movement of pedestrians and vehicles. Convenience of circulation und safety must be considered and panned together. A housing site should be provided with a periphery road system sufficiently wide to allow the maximum number of vehicles to move freely at all times. This road system should accommodate all through traffic that is bypasing the site and all genenated by the housing development. Pedestrian walks should be functionally organized and follow the natural traffic patterns of pedestrians. Sufficient off street parking should be provided for the housing site. In general several moderate- sized parking areas are preferable to one or two large areas. Convenient areas to locate settlement are areas that urban infrastuctal systems are passed by. Infrastructure system includes electricity, gas, water, telephone, cable T.V., sanitary sewer, storm sewer. All these service lines should placed underground to minimize disruptions from bad weather and to improve the visual aspects of the landscape. City furniture plays and important role to meet the needs of consumers in public places. City furnitures distinguished in two parts. Those which depend on infrastructure and those independant from the infrastructure. These furnitures are lamps, bus stops, selling booths, traffic signs, direction signs, mail boxes, clocks, sitting elements, garbage cans flower stands, etc. Green areas are very important to integrate nature. People relax themselves by joining outdoor activities. The green areas are subgrouped as active and passive green areas. Active green areas are playlots, playgrounds, playfields, parks, community parks, citywide or district parks. Variation and number of green areas change according to population and its composition such as population of children, youth and elderly people. In the forth parth, applied standarts of natural and man made environment which have been determinated by studying and questionaring in Bahçeşehir settlement that is one of the big mass housing project in Turkey are campared with the standards of determinated natural and man-made environments in Turkey and other countries. XIV In the fifth part, a general evaluation of the master thesis is made as followes: 1. Bahçeşehir settlement is established in steep slope. There fore, the cost of construction is increased and movement of vehicles are affected in a negative. In addition, soil in Bahçeşehir settlement is clayey and calcareous rendering the poor variety of the flora. 2. Although, Bahçeşehir settlement is only 20 minutes away from the center of the city, mass transportation is done by private vehicles only, public servis are not available. 3. Adminisrative facilities aro nat constructed. All administrative units are distributed in rented villas or flats in the settlement. 4. Apart form a high school all educational facilies are avilable. However it is difficult to reach these building from some parts of the settlement. Social and cultural facilities and activities are insufficient. Garden Clup which is the only sorcial facility in the settlement is far from the center. 6. The health center is completed but isn't being run yet. An infirmary which gives service in appartment flat is insufficent for the whole community. 7. Main shopping center is not located in neighborhood. Number of daily shopping centers are in suf ficent and they don't have all the shops that meet consumers ' daily needs. 8. Circulation of pedestriands and vehicles problem is solved. However; more than fifty persent of families have two cars, but 1.2. parking lots are reserved. 9. Infrastructure system is completed, but has not been used for a long time. There fore; it has began to decay and there fore it is defective. Almost all of city furniture is in sufficient 10. Green areas and their quantity per person in the settlement are abouve the Turkish Standards. All the green areas belong to the administration of the xv settlement. Therefore inhabitants have begun to claim on public open areas. In addition there aren't enough playlots, playgrounds, playfields for children, youth and elderly people. Conciderig the evaluations and results mentioned above, some suggestions are made: 1. In big mass housing projects, If there is more than one neighborhood unit, each unit should be planned, organized within the neighborhood itself. 2. Choosing location of mass housing settlements, topographical research should be done very well sothat constructing in steep solpes can be prevented. These areas can be left as green areas. 3. In mass housing settlements it is necessary to organize institutionalize administrative units for the further development of the setlement. 4. Ownners' economical standards, customs and traditions determine their life style. They choose their dwelling according to the their habits. There fore; a wide investigation should be done. 5. Owners' needs should be investigated well so that planning can be done accordig since economic level, as well as education level determine necessities. 6. Green areas should be functioned according to the owners' needs. Private gardens should be given to satisfy ownership feelings. 7. The use of mass housing-satellite settlement applications in solving demographic, social, cultural economic and environmental problems in the suburban areas can not be denied. However it must be kept in mind that proper application depends on scientific research.
Evaluation Of Environment Standards In Mass Housing Settlements-bahçeşehir Mass Housing Model
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1995
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 1995
Keywords: Peyzaj tasarımı; Landscape design; Çevre faktörleri; Toplu konutlar; İstanbul-Bahçeşehir; Istanbul-Bahcesehir; Environmental factors; Mass houses